2016
DOI: 10.1016/j.agee.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Managing for species composition or diversity? Pastoral and free grazing systems in alkali steppes

Abstract: A B S T R A C TFree grazing and herding of local breeds have a long tradition in management and conservation of extended grassland habitats such as alkali steppes. However, there is a lack in studies evaluating the effects of grazing types and regimes on the vegetation composition and functional diversity. We selected Artemisia steppes, a widespread type of alkali steppes, to study the changes of vegetation composition and diversity along a grazing intensity gradient. We recorded the cover of vascular plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
2
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 47 publications
5
49
2
20
Order By: Relevance
“…The intensity of livestock grazing highly influences the impact on grasslands (Papanastasis et al 1998, 2016. Long-term heavy grazing of water buffaloes in the study area may have affected the cover and the botanical composition of grasslands, but to our knowledge, there is no published evidence for this.…”
Section: Study Areamentioning
confidence: 74%
See 1 more Smart Citation
“…The intensity of livestock grazing highly influences the impact on grasslands (Papanastasis et al 1998, 2016. Long-term heavy grazing of water buffaloes in the study area may have affected the cover and the botanical composition of grasslands, but to our knowledge, there is no published evidence for this.…”
Section: Study Areamentioning
confidence: 74%
“…Traditional grazing by local breeds should be considered as one of the most adequate options to achieve a proper management of biodiversity and related ecosystem services in grasslands , Jerrentrup et al 2015. Most information concerning low intensity grazing systems are provided in relation to cattle and/or sheep grazing (Metera et al 2010, Jerrentrup et al 2015, Török et al 2016, while information on other types of grazing animals, such as Mediterranean river buffaloes, are rather scarce (but see Napolitano et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, across a large study region, Haynes et al (2012) demonstrated that grazing strongly modified plant community composition due to the selection of palatable plants, with species diversity declining under increased grazing intensity. Similarly, Török et al (2016) found a marked difference in species composition under very high grazing intensity. Conversely, Golodets et al (2010) identified species similarity increasing between vegetation on sites recently from which grazing had been recently excluded.…”
Section: The Influence Of Grazing On Species Community Composition Anmentioning
confidence: 95%
“…Grazing is a disturbance which can threaten the ability of plant communities to maintain plant species richness and abundance and lead to an altered species composition (Olff and Ritchie, 1998;Walker et al, 2013;Yan et al, 2013;Török et al, 2016). Grazing alters plant diversity through mechanisms that influence local plant colonization ability and extinction dynamics (Olff and Ritchie, 1998;Alofs et al, 2014).…”
Section: Influence Of Grazing On Species Richness Abundance and Specmentioning
confidence: 99%
“…Additionally, excessive livestock often are slaughtered in autumn to ensure moderate grazing intensity during the winter when rangeland productivity is low (Galvin, 2009). These traditional management regimes are intended not only to ensure sustainable yield but also to keep forage digestibility high and promote diversity in the rangeland plant community (Glindemann et al, 2009;Teague et al, 2013;Török et al, 2016).…”
Section: Introductionmentioning
confidence: 99%